Diagnostic Techniques in Industrial Engineering (Management and Industrial Engineering,, 2018)
This book presents the most important tools, techniques, strategy and diagnostic methods used in industrial engineering. The current widely accepted methods of diagnosis and their properties are discussed. Also, the possible fruitful areas for further research in the field are identified.